Harnessing mechanobiology for kidney organoid research - Nauryzgaliyeva, Zarina; Goux Corredera, Iphigénie; Garreta, Elena; Montserrat, Nuria (Frontiers in Cell and Developmental Biology, 2023)
Recently, organoids have emerged as revolutionizing tools with the unprecedented potential to recreate organ-specific microanatomy in vitro. Upon their derivation from human pluripotent stem cells (hPSCs), organoids reveal the blueprints of human organogenesis, further allowing the faithful recapitulation of their physiology. Nevertheless, along with the evolution of this field, advanced research exposed the organoids' shortcomings, particularly regarding poor reproducibility rates and overall immatureness. To resolve these challenges, many studies have started to underscore the relevance of mechanical cues as a relevant source to induce and externally control hPSCs differentiation. Indeed, established organoid generation protocols from hPSCs have mainly relyed on the biochemical induction of fundamental signalling pathways present during kidney formation in mammals, whereas mechanical cues have largely been unexplored. This review aims to discuss the pertinence of (bio)physical cues within hPSCsderived organoid cultures, while deciphering their effect on morphogenesis. Moreover, we will explore state-of-the-art mechanobiology techniques as revolutionizing means for understanding the underlying role of mechanical forces in biological processes in organoid model systems.